Programa virtual Movimundo para mejorar la expresión corporal de niños de 3 años en una Institución Educativa de Trujillo, 2020 - Huayan Salvador, Treicy Pamela (2021)
The purpose of this research work was to design the proposal for the Movimundo virtual program in order to significantly improve body expression in 3-year-old children from an Educational Institution in Trujillo. This research was prepared from the needs identified during remote group activities with students, because the children stayed at home to avoid contracting the virus called Covid-19, this resulted in the lack of practice of the corporal expression, due to the fact that a distance education was carried out, which led us towards an educational innovation through the design of the proposal. The research was quantitative, with a descriptive propositional design, having as a sample 10 students from the 3-year-old classroom "E" of which 6 were girls and 4 were boys. A rubric was applied to evaluate the corporal expression of the children, having as results: 0 children located in the high level represented by 0%, 7 children located in the medium level represented by 70% and 3 children located in the low level represented by 30%, which confirms the development of the Movimundo virtual program proposal to improve body expression in 3- year-old children in an IE in Trujillo, 2020.